1994
DOI: 10.1093/nar/22.13.2479
|View full text |Cite
|
Sign up to set email alerts
|

Modular sequence elements associated with origin regions in eukaryotic chromosomal DNA

Abstract: We have postulated that chromosomal replication origin regions in eukaryotes have in common clusters of certain modular sequence elements (Benbow, Zhao, and Larson, BioEssays 14, 661-670, 1992). In this study, computer analyses of DNA sequences from six origin regions showed that each contained one or more potential initiation regions consisting of a putative DUE (DNA unwinding element) aligned with clusters of SAR (scaffold associated region), and ARS (autonomously replicating sequence) consensus sequences, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 106 publications
(77 reference statements)
8
60
0
Order By: Relevance
“…Subsequent work has confirmed that replication starts in this location and at additional sites over a 12-kb region encompassing the c-myc gene (27,29,33,(38)(39)(40)(41). The 2.4-kb c-myc origin fragment contains a DNA unwinding element (DUE), which is a common feature of eucaryotic origins (11), a unique nucleosome organization, and three matches to the S. cerevisiae autonomously replicating sequence (ARS) consensus (39). Plasmids containing the 2.4-kb fragment of the c-myc origin replicate autonomously in vitro and when transfected into HeLa cells (3,16,27).…”
mentioning
confidence: 89%
“…Subsequent work has confirmed that replication starts in this location and at additional sites over a 12-kb region encompassing the c-myc gene (27,29,33,(38)(39)(40)(41). The 2.4-kb c-myc origin fragment contains a DNA unwinding element (DUE), which is a common feature of eucaryotic origins (11), a unique nucleosome organization, and three matches to the S. cerevisiae autonomously replicating sequence (ARS) consensus (39). Plasmids containing the 2.4-kb fragment of the c-myc origin replicate autonomously in vitro and when transfected into HeLa cells (3,16,27).…”
mentioning
confidence: 89%
“…The boundary locus 5'-TAAAAAAATA-Y is homologous to the consensus sequence found in Matrix Attachment Regions (MARs) and potential replication-initiation regions [10]. Alignment with five sequenced members of the HRS60 family shows (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…3) where the helical stability of the duplex, as measured by the ⌬G value, is at least 25 kcal/mol less than the average value for the whole sequence (95.9 kcal/mol). DUEs are known to be associated with eukaryotic replication origins, as its intrinsic helical instability facilitates replication initiation (8). DUEs are also a feature of S/MARs due to their property of stress-induced duplex destabilization, which is essential for S/MAR function (3).…”
Section: Resultsmentioning
confidence: 99%